Unsteady streaming flow based TENG using hydrophobic film tube with different charge affinity. (January 2020) - Ahn, Jee Hwan; Hwang, Jeong Yun; Kim, Chang Gon; Nam, Gyu Hyeon; Ahn, Kyoung Kwan
Abstract: This paper proposes a simple, eco-friendly and economical fluid-based triboelectric nanogenerator (Flu-TENG), which is based on polyvinylidene fluoride (PVDF) between elastomeric tubes (P-TENG) and biaxially oriented polypropylene (BOPP) between elastomeric tubes (B-TENG). We examined the interactions based on the relation between the hydrodynamics of pipe flow and electrostatic induction at the electrical double layer (EDL). This is the first study to focus on the hydrodynamics of the unsteady pipe flow. From the experimental results, it was verified that the peak to peak current from unsteady flow is 70 times higher than that of steady flow. We also investigated the effect of triboelectric series to generate higher output. When the PVDF and Ground/PVDF/BOPP are connected respectively, it is called as P-TENG/PP-TENG/PB-TENG. The measured short circuit current at 15.9 Hz for P-TENG/PP-TENG/PB-TENG are 0.29 μA, 1.59 μA and 2.40 μA, respectively. And the measured open circuit voltage of P-TENG/PP-TENG/PB-TENG are 3.71 V, 14.6 V and 29.7 V, respectively. Finally, we verified the maximum power reaches 11.5 μW in the case of PB-TENG. This provides a new approach for improving the output power of the FluTENG for special applications. Graphical abstract: Image 1 Highlights: A novel PB-TENG utilizing unsteady fluctuating flow has been proposed. The mechanism of energy harvesting in unsteady streaming flow is investigated. It was verified that current output of unsteady flow is 70 times larger than that of steady. Maximum RMS power has been achieved up to 11.5 μW for PB-TENG and 8.1 μW for PG-TENG.